Nucleic acid methylation and orofacial morphogenesis. Issue 20 (5th August 2019) - Seelan, Ratnam S.; Pisano, Michele; Greene, Robert M.
Abstract: In this review, we highlight the current state of knowledge of the diverse roles nucleic acid methylation plays in the embryonic development of the orofacial region and how aberrant methylation may contribute to orofacial clefts. We also consider the role of methylation in the regulation of neural crest cell function as it pertains to orofacial ontogeny. Changes in DNA methylation, as a consequence of environmental effects, have been observed in the regulatory regions of several genes, potentially identifying new candidate genes for orofacial clefting and opening promising new avenues for further research. While the focus of this review is primarily on the nonsyndromic forms of orofacial clefting, syndromic forms are briefly discussed in the context of aberrant nucleic acid methylation.